Talent is never enough: a preliminary qualitative data analysis - Orsolic, M.; Barbaros, P.; Novak, D. (Collegium Antropologicum, 2021)
Sports development of young and talented athletes is a very dynamic process which includes an ample range of challenges and obstacles. The aim of this research is a qualitative analysis of experiences of tennis players` with a lower-range of efficiency as senior players. The attempt was to identify those factors that prevented efficiency in senior competitions for tennis players who achieved excellent results in junior competitions. Particular emphasis was directed towards three domains which were presented as key factors for a successful athletic career in previous research (specialisation in the chosen sport, environmental impact on sports development and negative life events/circumstances). A series of polystructural interviews with tennis players in senior competitions were conducted (N = 10). The obtained data indicate several factors with a negative impact on the successful development of young and talented tennis players, as follows: premature specialisation, insufficient commitment to the training process, lack of adequate support by the parents and coach, failure to make proper and timely decisions regarding one`s own sports development, injuries and insufficient financial means. The identification of key factors in the sports development of young athletes can be of crucial relevance for quality guidance and direction in sports careers of talented athletes.